HUBUNGAN PENGETAHUAN IBU, DUKUNGAN SUAMI DAN EFEK SAMPING DENGAN PENGGUNAAN KONTRASEPSI INTRA UTERINE DEVICE (IUD) DI PUSKESMAS PEDAMARAN TIMUR KABUPATEN OKI TAHUN 2020 - Paula, Yuan (Program Studi Ilmu Kesehatan STIKESÂ Abdi Nusa Pangkalpinang, 2020)
The intrauterine device (IUD) is a small, flexible plastic material that is inserted into the uterine cavity and must be replaced if it has been used for a certain period of time. The purpose of this study was to determine the relationship between Maternal Knowledge, Husband Support and Side Effects with the use of intra-uterine device (IUD) contraceptives at Puskesmas Pedamaran Timur, OKI Regency in 2020. The design of this study used quantitative with a